KAJIAN FAKTOR MIGRASI INTERNASIONAL TERHADAP TENAGA KERJA INDONESIA DI KABUPATEN KULON PROGO, YOGYAKARTA, INDONESIA - Sudibyo, Tahajudin; Satris, Rezki; Amrullah, Yusuf Amri (Dauliyah: Journal of Islam and International Affairs, 2022)
This research presents various problems faced by the international community, one of which is migration. International migration is studiedfrom a functionalist perspective based more on the general social, economiccharacteristics of the community in the region and in the work destinationcountry, both individually and in groups in the decision-making process.International migration is based on various factors, namely poverty,unemployment, high motivation and the desire to change economic status.This study uses a qualitative approach, which uses descriptive to convey thevalue and results of the study. The sources used in this research are literatureboth from journals and from books that contain studies on internationalmigration. In addition, all the data used in this study is social media data.From this analysis it is found that the four indicators of the functionalist studyhave a dominant influence on people to work as Indonesian workers.